A study on the specificity of the association between hippocampal volume and delayed primacy performance in cognitively intact elderly individuals. (March 2015) - Bruno, Davide; Grothe, Michel J.; Nierenberg, Jay; Zetterberg, Henrik; Blennow, Kaj; Teipel, Stefan J.; Pomara, Nunzio
Abstract: Delayed recall at the primacy position (first few items on a list) has been shown to predict cognitive decline in cognitively intact elderly participants, with poorer delayed primacy performance associated with more pronounced generalized cognitive decline during follow-up. We have previously suggested that this association is due to delayed primacy performance indexing memory consolidation, which in turn is thought to depend upon hippocampal function. Here, we test the hypothesis that hippocampal size is associated with delayed primacy performance in cognitively intact elderly individuals. Data were analyzed from a group ( N =81) of cognitively intact participants, aged 60 or above. Serial position performance was measured with the Buschke selective reminding test (BSRT). Hippocampal size was automatically measured via MRI, and unbiased voxel-based analyses were also conducted to explore further regional specificity of memory performance. We conducted regression analyses of hippocampus volumes on serial position performance; other predictors included age, family history of Alzheimer's disease (AD), APOE ε4 status, education, and total intracranial volume. Our results collectively suggest that there is a preferential association between hippocampal volume and delayed primacy performance. These findings are consistent with the hypothesis that delayed primacy consolidation is associated with hippocampal size, and shed light on the relationship between delayed primacy performance and generalized cognitive decline in cognitively intact individuals, suggesting that delayed primacy consolidation may serve as a sensitive marker of hippocampal health in these individuals. Highlights: The study sample constituted cognitively intact adults aged 60 or higher. Delayed free recall for primacy words was associated with hippocampal volume. This association was weaker for delayed non-primacy performance.